Intermediate C# programming : a foundational approach to learning C# - Lippert, Eric; Safari eBooks ([Place of publication not identified] : O'Reilly, 2015)
"In this follow-up to his popular Beginning C# Programming video, former Microsoft developer and C# expert Eric Lippert introduces you to intermediate-level C# concepts and practices through a series of helpful examples, exercises, and projects. This hands-on video course takes you into more complex examples of object-oriented programming, as well as types, file management, and event-driven programming--including the creation of a graphical user interface (GUI). To provide you with a smooth transition from his earlier video, Eric reviews topics from the Beginning course, including values, variables, arrays, statements, loops, and writing specifications. Through the course of the Intermediate C# Programming video, you will: learn about generic collection types, such as lists and dictionaries, and enumerated types that represent things like days of the week; dive into file management and learn how to use text files and embedded resources; understand the types of problems OOP was designed to solve Work with OOP classes, constructors, fields, methods, virtual methods, object properties, type checking, and inheritance; explore the five SOLID principles of good OOP design, and check to see if your work adheres to them; use event-driven programming with Windows Presentation Foundation to create a GUI."--Resource description page.
Title from title screen (viewed September 9, 2015).
Publication date taken from resource description page.
Presenter, Eric Lippert.
Keywords: C# (Computer program language); Object-oriented programming (Computer science); Electronic books